The Effect of Gender Inequality in Education on Rural Poverty: A Case Study of Nyakagyeme Sub-County Rukungiri District. - Akaruhanga, Jasper (Kabale University, 2024)
The study focused on the findings of the effect of gender inequality in education on rural poverty of Nyakagyeme sub-county, Rukungiri district. The objectives of the study included the following: to investigate the cause of gender inequality in education and rural poverty of Nyakagyeme sub-county, Rukungiri district, to find out the effects of gender inequality on education and rural poverty of Nyakagyeme sub-county, Rukungiri district and to identify possible solutions that have been suggested on education and rural poverty in of Nyakagyeme sub-county, Rukungiri district. There was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on gender inequality as an independent variable and education on rural poverty as the dependent variable and the methods of data collection were put into action. The research used 80 respondents as the sample size, and both qualitative and quantitative methods of data collection and analysis were employed. The researcher used simple random sampling techniques in collecting and analyzing data and was used to provide equal chances to the sample size. Purposive sampling was also used to collect data from respondents who participated in the study. Findings of the study were obtained from the field interpreting the results analyzing based on the specific objectives of the study chapter five portrayed the summary of findings, and recommendations were made such as the Ministry of Labor, Gender and Social Development should address the problem of poverty concerning gender inequality among women in Uganda, there should be awareness raising regarding gender-based violence, the gender inequality should be addressed through social protection programs like equal enjoyment of social services for example clean water in the community, for women to contribute in the development process their potential should be unfolded by sensitizing them about development and providing them with necessary knowledge to help them to be included in the development process and women should get access to economic assets like land and houses that can be used as collateral to secure soft loans